Fibroblast Growth Factor in Diabetic Foot Ulcer: Progress and Therapeutic Prospects - Liu, Ye; Liu, Yiqiu; Deng, Junyu; Li, Wei; Nie, Xuqiang (Frontiers in Endocrinology, 2021)
Diabetic foot ulcer (DFU) is a combination of neuropathy and various degrees of peripheral vasculopathy in diabetic patients resulting in lower extremity infection, ulcer formation, and deep-tissue necrosis. The difficulty of wound healing in diabetic patients is caused by a high glucose environment and various biological factors in the patient. The patients’ skin local microenvironment changes and immune chemotactic response dysfunction. Wounds are easy to be damaged and ulcerated repeatedly, but difficult to heal, and eventually develop into chronic ulcers. DFU is a complex biological process in which many cells interact with each other. A variety of growth factors released from wounds are necessary for coordination and promotion of healing. Fibroblast growth factor (FGF) is a family of cell signaling proteins, which can mediate various processes such as angiogenesis, wound healing, metabolic regulation and embryonic development through its specific receptors. FGF can stimulate angiogenesis and proliferation of fibroblasts, and it is a powerful angiogenesis factor. Twenty-three subtypes have been identified and divided into seven subfamilies. Traditional treatments for DFU can only remove necrotic tissue, delay disease progression, and have a limited ability to repair wounds. In recent years, with the increasing understanding of the function of FGF, more and more researchers have been applying FGF-1, FGF-2, FGF-4, FGF-7, FGF-21 and FGF-23 topically to DFU with good therapeutic effects. This review elaborates on the recently developed FGF family members, outlining their mechanisms of action, and describing their potential therapeutics in DFU.